2021
DOI: 10.4049/jimmunol.2001062
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Receptors as Immune Modulators

Abstract: The Coronaviridae family includes the seven known human coronaviruses (CoV) that cause mild to moderate respiratory infections (HCoV-229E, HCoV-NL63, HCoV-OC43, HCoV-HKU1) as well as severe illness and death (MERS-CoV, SARS-CoV, SARS-CoV-2). Severe infections induce hyperinflammatory responses that are often intensified by host adaptive immune pathways to profoundly advance disease severity. Proinflammatory responses are triggered by CoV entry mediated by host cell surface receptors. Interestingly, five of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 118 publications
0
10
0
3
Order By: Relevance
“…We evaluated the performance of phage mimicry using representatives of major classes of cell surface receptors, which mediate entry of coronaviruses into the host cells: (1) metallopeptidases, including angiotensin-converting enzyme 2 (ACE2) [1,26], and (2) growth factor receptors, including fibroblast growth factor receptor 3 (FGFR3) [35,37,[78][79][80][81].…”
Section: Landscape Phage Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the performance of phage mimicry using representatives of major classes of cell surface receptors, which mediate entry of coronaviruses into the host cells: (1) metallopeptidases, including angiotensin-converting enzyme 2 (ACE2) [1,26], and (2) growth factor receptors, including fibroblast growth factor receptor 3 (FGFR3) [35,37,[78][79][80][81].…”
Section: Landscape Phage Librariesmentioning
confidence: 99%
“…The evolution of the SARS-CoV-2 virus during the COVID-19 pandemic was accompanied by the emergence of a diverse assortment of new virus variants having multiple mutations in both receptor-and antibody-binding sites located throughout the spike S protein (Figure 1). Analysis of a variety of coronavirus variants that caused epidemics during the last 60 years showed that their evolution may occur not only through the appearance and selection of immuno-resistant mutants, but also by the selection of variants with altered spike proteins that can use alternative, or "reserve", human host receptors for entering into target cells [18,[26][27][28][29]. Our current understanding of the molecular mechanisms of virus adaptation to human host cells [30] and immuno-resistant human populations is not sufficient to rationally design efficient countermeasures against viral pandemics, such as the SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 99%
“…CD13, CD24, and CD82 are involved in inflammatory processes (Barkal et al., 2019; Lu et al., 2020; Yeung et al., 2018). CD13 is known receptor for several corona viruses (Devarakonda et al., 2021; Nomura et al., 2004; Pƶhlmann et al., 2006; Qi et al., 2020) and associated with several EVs types, including ones from, that is, synoviocytes, endometrial epithelial cells, microglia, urine, plasma, leukocytes and umbilical cordā€derived mesenchymal stromal cells (ErdbrĆ¼gger et al., 2021; Lin et al., 2020; Morgan et al., 2016; Priya et al., 2021; Potolicchio et al., 2005; Romanov et al., 2018; TőkĆ©sā€FĆ¼zesi et al., 2018; Yoshihara et al., 2021). The tetraspanin CD82 is a constituent of tetraspaninā€enriched membrane domains (TEMs, which represent the places of entry/egress of some viruses) but also responsible for immune cells recruitment, migration (Yeung et al., 2018) and acts as a costimulatory molecule for T cells (Earnest et al., 2017; Florin & Lang, 2018; ProteinAtlas: CD82; Sims et al., 2018; YƔƱezā€MĆ³ et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…However, some mild patients also experienced a cytokine storm due to immune disorders. This involves a suicide attack that can damage the virus but also leave behind collateral damage, which will eventually lead to further lung injury, multiple organ failure and even increase the risk of death ( 96 ). Therefore, monitoring the level of pro-inflammatory cytokines and taking corresponding intervention measures as early as possible is of great significance to delay the transformation of mild or moderate patients to severe patients and also to achieve good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%